Performance Analysis of Provider and Riverpod State Management Library on Flutter Applications - Puryanto, Jonathan Aditya; Akbar, Habibullah (Journal of Technology and Informatics (JoTI), 2025)
State management libraries are essential components in Flutter app development. This research aims to compare the performance of the state management library Provider and its successor, Riverpod, to assist Flutter developers in choosing the right solution. Two versions of the MovieDB app were built, each utilizing Provider and Riverpod. Performance testing was conducted using three metrics: CPU Utilization, Memory Usage, and Execution Time, across three data volumes (1,000, 5,000, and 10,000). The results showed that CPU Utilization varied by only 0.1–0.2% with Riverpod being slightly more efficient at 1,000 and 10,000 data volumes. Execution Times also showed minimal differences, with Riverpod being marginally faster by approximately 0.01 seconds at 5,000 and 10,000 data volumes. Riverpod excelled in Memory Usage, demonstrating an average reduction of about 3–6% across all data volumes, particularly at higher data volumes. In conclusion, the performance of both libraries is fundamentally similar, but Riverpod is offers better memory efficiency and architectural flexibility. Therefore, Riverpod is recommended for new projects, while Provider remains a viable option for stable existing applications that already use it.